2017
DOI: 10.1016/j.bbr.2016.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating effect of EUK-207 on radiation-induced cognitive impairments

Abstract: The brain could be exposed to irradiation as part of a nuclear accident, radiological terrorism (dirty bomb scenario) or a medical radiological procedure. In the context of accidents or terrorism, there is considerable interest in compounds that can mitigate radiation-induced injury when treatment is initiated a day or more after the radiation exposure. As it will be challenging to determine the radiation exposure an individual has received within a relatively short time frame, it is also critical that the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…To probe the impact of ROS mitigation on H 2 O 2 -induced DNA damage and senescence-like phenotypes, we tested a synthetic SOD/catalase mimetic, EUK-207. This molecule possesses both SOD and catalase activity and scavenges ROS generated in the cytoplasm or organelles, including the mitochondria [17]. In addition, EUK-207 suppresses oxidative modifications of proteins, lipids, and nucleic acids [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To probe the impact of ROS mitigation on H 2 O 2 -induced DNA damage and senescence-like phenotypes, we tested a synthetic SOD/catalase mimetic, EUK-207. This molecule possesses both SOD and catalase activity and scavenges ROS generated in the cytoplasm or organelles, including the mitochondria [17]. In addition, EUK-207 suppresses oxidative modifications of proteins, lipids, and nucleic acids [61].…”
Section: Discussionmentioning
confidence: 99%
“…EUK-207 suppresses oxidative stress, including in the mitochondria [13, 14], through transforming oxygen free radicals into oxygen via a superoxide dismutase-like activity, and hydrogen peroxide into oxygen and water by a catalase-like activity [13]. EUK-207 has been used successfully to suppress age-related [15, 16] and radiation-induced cognitive impairment in mice [17].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies were focused on the manganosalen EUK-207 due to both its ability to suppress oxidative stress and its greater biological stability. Thus, Raber et al [ 114 ] reported that this compound mitigated radiation-induced cognitive impairments without affecting cognition of sham-irradiated mice. Wang et al [ 22 , 115 ] used EUK-207 to treat hydrogen peroxide-induced DNA damage and senescence phenotype in senescence-accelerated mouse-prone 8 mice, reducing age-related loss of both hearing and hair cell degeneration.…”
Section: Therapeutic Effects Of Manganosalen Complexes In In Vivo mentioning
confidence: 99%
“…More recent studies were focused on the manganosalen EUK-207, due to both its ability to supress oxidative stress and its greater biological stability. Thus, Raber et al [117] reported that this compound mitigated radiation-induced cognitive impairments without affecting cognition of shamirradiated mice. Wang et al [22,118] used EUK-207 to treat hydrogen peroxide induced DNA damage and senescence phenotype in senescence-accelerated mouse-prone 8 mice, reducing age-related loss of both hearing and hair cells degeneration.…”
Section: Neurodegenerative Diseases and Mental Disordersmentioning
confidence: 99%